Nutritional aspects of immunosuppression in athletes - Bishop, N. C.; Blannin, A. K.; Walsh, N. P.; Robson, P. J.; Gleeson, M. (Sports Medicine, 1999)
The literature suggests that a heavy schedule of training and competition leads to immunosuppression in athletes, placing them at a greater risk of opportunistic infection. There are many factors which influence exercise-induced immunosuppression, and nutrition undoubtedly plays a critical role. Misinterpretation of published data and misleading media reports have lead many athletes to adopt an unbalanced dietary regimen in the belief that it holds the key to improved performance. Some sports have strict weight categories, whilst in others low body fat levels are considered to be necessary for optimal performance or seen as an aesthetic advantage. This leads some athletes to consume a diet extremely low in carbohydrate content which, whilst causing rapid weight loss, may have undesirable results which include placing the athlete at risk from several nutrient deficiencies. Complete avoidance of foods high in animal fat reduces the intake of protein and several fat-soluble vitamins. On the other hand, diets with a very high carbohydrate content are usually achieved at the expense of protein. In addition, anecdotal and media reports have often promoted the supposed performance benefits of certain vitamins and minerals, yet most athletes do not realise that micronutrient supplementation is only beneficial when correcting a deficiency, and to date there is little scientific evidence to substantiate claims that micronutrients act as an ergogenic aid. Moreover, excessive intakes of micronutrients can be toxic. Deficiencies or excesses of various dietary components can have a substantial impact on immune function and may further exacerbate the immunosuppression associated with heavy training loads. This review examines the role of nutrition in exercise-induced immunosuppression and the effect of both excessive and insufficient nutrient intake on immunocompetence. As much of the present literature concerning nutrition and immune function is based on studies with sedentary participants, the need for future research which directly investigates the relationship between exercise, training, immunity and nutrition is highlighted.